Innovations at the Borderline of Food, Nutrition and Health in Germany - A Systems' Theory Approach - Klaus Menrad (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
This article deals with the innovation system in Germany at the borderline of food, nutrition and health. After an overview over existing concepts to analyse innovations in system theory, the major factors (technologies, economic competence, institutional infrastructure, development block) are studied which determine the innovation system in this area in Germany. Afterwards recommendations are outlined on how to modify the innovation system in future.
Keywords: 330; Ernährungsindustrie; Funktionelle Lebensmittel; Innovation; Forschungskooperation; Systemtheorie; Deutschland